To boldly go: the next generation of the Digital Mineral Library at Curtin University - Liffers, Matthias; McInnes, Brent I.A.; Brown, Adam (Curtin University, 2016)
After its success with the Australian National Data Service (ANDS)-funded Major Open Data Collection (MODC) project, Curtin University is working on the next phase of the Digital Mineral Library to integrate data from the SHRIMP ion microprobe, encourage greater data sharing among geoscientists and expand the coverage of the collection.